Navigating an early career in genomics and data science, written from the perspective of a current PhD student - Tooze, R (Cell Press, 2022)
Rebecca Tooze, a PhD student in the Oxford Clinical Genetics’ group, discusses the importance and application for data science in her field. Using bioinformatic approaches, she analyzes whole-genome sequencing data from patients with craniosynostosis. In this paper, she comments on her current research and her opportunity as an editorial intern with Patterns.